Medborgardialog i Luleå kommun : En studie om politisk delaktighet - Gustafsson, Karin (2014)
The purpose of this study is to examine Citizen Dialogue and how it promotes political participation. The study is based on a literature review of policy documents and relevant theories. The analysis is complemented by a qualitative study of how Luleå Municipality are initiating public dialogue.The basic idea of democracy is that political decisions should be based on human rights with free and equal citizens. By initiating Citizen Dialogue, this becomes possible. Since 2007, the development of Citizen Dialogue in Sweden has been performed. Each municipality and county councils are responsible for initiating public dialogue, with SKL 's support. SKL has developed methods and models that can help in this work process. In this paper I present the theory behind and the recent work on Citizen Dialogue, with SKL as my main focus. Dialogue with citizens promotes, like democracy, to political participation and human rights. Parallels are drawn to Citizen Dialogue and deliberative democracy. A discussion about the power relationship in the dialogue are also made, like power of manipulation and control of the agendaTo examine how the initialization of Citizen Dialogue within a community might look like in practice, a study of how Luleå Municipality used Citizen Dialogue in their town was made. In Luleå, they have had dialogues with the citizens for several years. How the dialogue have seen and looked may vary between the different administrations of the municipality. Since the year 2013, Luleå have had the intention to develop and create a structure for Citizen Dialogue that becomes valid for all departments in the municipality. Development areas are early initiation of dialogue to increase the level of citizens' influence, reach more citizens than those who voluntarily participate in the dialogue and increase politicians' involvement in the dialogue process. Validerat; 20140918 (global_studentproject_submitter)